Thoraco-epigastric flap for breast reconstruction in cancer - A. D. Zikiryakhodzhayev,; E. K. Saribekyan; E. A. Rasskazova (Опухоли женской репродуктивной системы, 2015)
Reconstructive surgery for breast cancer are an integral method of rehabilitation of cancer patients. Breast reconstruction may be delayed and instantaneous. The article presents a description of the thoraco-epigastric flap for breast reconstruction in cancer. The operation involves the replacement of the remote volume (after radical resection of the breast) and the breast skin adjacent tissues adjacent to the inframammary crease from the side of the anterior abdominal wall. Surgery is indicated when the tumor in the lower parts of the breast, closest to the skin, in combination with small size breast cancer. The article presents a clinical example of this operation. Described in detail the operation, received a good cosmetic result. The advantage of the application of thoraco-epigastric flap is in the simplicity of the technique of its execution, good blood supply, donor wound is easily sutured due to the possible wide separating cellular adjacent skin and subcutaneous tissue. The disadvantage of this method is limited and the need for careful monitoring of perforating branches of the upper epigastric artery. Thus, thoraco-epigastric flap, can be applicable when performing reconstructive operations for breast cancer in compliance with the necessary requirements for the formation of the flap and the correct attitude to feeding the flap vessels, and virtually eliminates possible complications with the healing of the flap. Undoubtedly, reconstructive plastic surgery for breast cancer, during the testimony and technical capabilities, are an essential component of surgical treatment.